Relaxation of the non-photochemical chlorophyll fluorescence quenching in diatoms: kinetics, components and mechanisms - Roháček, Karel; Bertrand, Martine; Moreau, Brigitte; Jacquette, Boris; Caplat, Christelle; Morant-Manceau, Annick; Schoefs, Benoît (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2014)
Diatoms are especially important microorganisms because they constitute the larger group of microalgae. To survive the constant variations of the light environment, diatoms have developed mechanisms aiming at the dissipation of excess energy, such as the xanthophyll cycle and the non-photochemical chlorophyll (Chl) fluorescence quenching. This contribution is dedicated to the relaxation of the latter process when the adverse conditions cease. An original nonlinear regression analysis of the relaxation of non-photochemical Chl fluorescence quenching, qN, in diatoms is presented. It was used to obtain experimental evidence for the existence of three time-resolved components in the diatom Phaeodactylum tricornutum: qNf, qNi and qNs. qNf (s time-scale) and qNs (h time-scale) are exponential in shape. By contrast, qNi (min time-scale) is of sigmoidal nature and is dominant among the three components. The application of metabolic inhibitors (dithiothreitol, ammonium chloride, cadmium and diphenyleneiodonium chloride) allowed the identification of the mechanisms on which each component mostly relies. qNi is linked to the relaxation of the ΔpH gradient and the reversal of the xanthophyll cycle. qNs quantifies the stage of photoinhibition caused by the high light exposure, qNf seems to reflect fast conformational changes within thylakoid membranes in the vicinity of the photosystem II complexes.
Keywords: chlorid amonný; Kinetics; xanthofyly; relaxation; regresní analýza; oniové sloučeniny; Chlorophyll; rozsivky; xanthophyll cycle; high light stress; photosynthesis; Thylakoids; Fluorescence; světlo; Time Factors; chlorofyl; dithiothreitol; kinetika; tylakoidy; Ammonium Chloride; časové faktory; Diatoms; Onium Compounds; Photosystem II Protein Complex; diatom; Dithiothreitol; Regression Analysis; kadmium; Light; Xanthophylls; fluorescence; photoprotection; fotosystém II (proteinový komplex); Cadmium